2005
DOI: 10.1080/014850190512798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on Female Sexual Function and Risk Factors

Abstract: The study was conducted to investigate the effect of diabetes mellitus upon female sexual function, and to detect possible risk factors that might predict sexual dysfunction. The study consisted of 127 married women: 21 women with type 1 diabetes, 50 women with type 2 diabetes and 56 healthy women as a control. Female sexual functions were evaluated with a questionnaire to assess sexual desire, arousal, lubrication, orgasm, satisfaction and pain. The prevalence of sexual dysfunction was 71% in the type 1 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
117
6
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 27 publications
17
117
6
4
Order By: Relevance
“…Resultados discordantes são encontrados na literatura 9,22,[25][26][27] , mostrando que essas doenças estariam associadas aos piores escores de sexualidade. Tais resultados discrepantes podem ser atribuídos às diferenças metodológicas encontradas quanto ao tipo de questionário empregado (Short Personal Experiences Questionnaire 9 e FSFI 20,22,[25][26][27] ), à característica da população incluída (escolaridade mínima de 11 anos 9 , mulheres chinesas 20,27 , mais de 20 anos 22 , 20 a 60 anos 27 , sem outras morbidades 27 , tipo de diabetes 26,27 ) e ao tipo de análise utilizada (regressão logística 20,27 ).…”
Section: Discussionunclassified
“…Resultados discordantes são encontrados na literatura 9,22,[25][26][27] , mostrando que essas doenças estariam associadas aos piores escores de sexualidade. Tais resultados discrepantes podem ser atribuídos às diferenças metodológicas encontradas quanto ao tipo de questionário empregado (Short Personal Experiences Questionnaire 9 e FSFI 20,22,[25][26][27] ), à característica da população incluída (escolaridade mínima de 11 anos 9 , mulheres chinesas 20,27 , mais de 20 anos 22 , 20 a 60 anos 27 , sem outras morbidades 27 , tipo de diabetes 26,27 ) e ao tipo de análise utilizada (regressão logística 20,27 ).…”
Section: Discussionunclassified
“…60,61 FSD affects 30-50% of women and correlates with age, education, physical and emotional health. 17,31,62 Older women screened for sexual concerns during a routine gynecological visit reported a similar number of concerns as younger women. Women of any age reported decreased sexual desire, sexual aversion and desires different from their partners, unmet sexual needs and having had or considering having an affair.…”
Section: Sd With Age In Womenmentioning
confidence: 96%
“…30 The prevalence of SD is also high in diabetic women and more prevalent with age and low-grade education. 31 High total cholesterol and LDL cholesterol in men older than 40 were associated with ED in contrast to younger men and controls suggest that hyperlipidemia explains, in part, ED with age. 32 Hypertension causes endothelial dysfunction, and is associated with ED.…”
Section: Sd and Diseasementioning
confidence: 99%
“…[43][44][45]47,51,52 The incidence of arousal problems in women with diabetes is also variable, depending on the type of diabetes and the definition of arousal, and varies from 14 to 76% to no effect at all. [42][43][44][45][46][47]49,51,52 Regarding orgasm, most studies have indicated problems in women with diabetes ranging from 10-84%, [43][44][45][46]49 with a few studies showing no effect. 56 Finally, the risk of dyspareunia in women with diabetes varies from zero to 43%, with the higher prevalence being observed in type 2 diabetes.…”
Section: Diabetes Mellitus and Female Sexual Dysfunctionmentioning
confidence: 99%
“…42,49,50 in several ethnic groups (US, Italian, Polish, Turkish, Iranian, Jordanian, Nigerian, Peruvian populations) have reported a high prevalence of sexual dysfunction in women with either type 1 or type 2 diabetes. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] These data are important since various cultures, religions, lifestyle habits and sexual behaviours are considered. Although the prevalence varies (Table 1) 40,42-53 depending on the criteria used to define sexual dysfunction in each study, it appears that sexual dysfunction is slightly lower in women compared to men, 13,54,55 it is twice that of the population without diabetes, 13,40,45,48,56 and it includes all the domains of sexual dysfunction.…”
Section: Diabetes Mellitus and Female Sexual Dysfunctionmentioning
confidence: 99%